Political leadership, nascent statehood and democracy : a comparative study - Moller, Ulrika; Schierenbeck, Isabell (Abingdon, Oxon : Routledge, 2014)
'Do political leaders determine whether a polity will receive a democratic future or not? Research and advocates of democracy agree on the significance of political elites for democratization, yet there is a need for a more specific understanding of their role.This book develops a theory of political leadership at the point of nascent statehood to explain the emergence of resilient democracies. It employs four diverse case studies to examine the role of leadership and democratic consolidation. In doing so, the book identifies certain capacities of political leaders at the critical moment of nascent statehood as decisive to the future democratic quality of their state. This book will be of interest to students and scholars of international relations, democratization studies, state building, leadership, nationalism, Middle Eastern studies and South Asian studies'--
The success and failure of democratic state building -- Situating the study -- Introduction to the cases -- India -- Pakistan -- Israel -- Palestine -- Summary of results and case comparison -- Implications for th efuture democratic state project.
Includes bibliographical references (p. 179-193) and index.
Keywords: Political leadership -- Case studies; Nation-state -- Case studies; Democracy -- Case studies; Democratization -- Case studies; India -- Politics and government; Pakistan -- Politics and government; Israel -- Politics and government; Palestine -- Politics and government